2023
DOI: 10.36227/techrxiv.22094579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Transcutaneous Spinal Cord Stimulation on Balance and Neurophysiological Characteristics in Young Healthy Adults

Abstract: <p>This article describes the effects of combining perturbation based balance training and transcutaneous spinal cord stimulation (TSCS) on postural balance control. </p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The effect of spinal tES on balance control was studied in healthy adults [ 25 , 26 ]. The tests included forward, backward, and left and right trunk perturbations with and without midline stimulation between the L2 and L3 vertebrae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of spinal tES on balance control was studied in healthy adults [ 25 , 26 ]. The tests included forward, backward, and left and right trunk perturbations with and without midline stimulation between the L2 and L3 vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Life 2023, 13,1909 12 of 14 We have shown that tES of the spinal cord at the L1-L2 vertebrae reduces postural control during quiet standing when the "equilibrium" task is virtually absent. Omofuma and colleagues [25,26] stimulated a similar level of the spinal cord and tested balance control during trunk perturbations when the "equilibrium" task was solved simultaneously with the "posture" task. They found that balance suffered.…”
Section: Limitationsmentioning
confidence: 99%